Frecuencia de parásitos gastrointestinales en equinos en cinco veredas del municipio de Almaguer - Cauca en el periodo 2023 - 2 (2024)
During the months of August to November 2023, an investigation was carried out on the frequency of gastrointestinal parasites in horses in five villages of the municipality of Almaguer, out of a total population (280 animals) of these villages, a sample of 100 was taken 20 animals were obtained for each village, individually samples were collected directly from the animal's rectum. They were taken to the laboratory of the San Luis and Santa María schools and processed through the flotation test. 100% samples 88% were positive and 12% negative, of which 95% were in the Cerro Largo village positive and 5% negative, Caquiona 95% positive and 5% negative, Buena Vista 95% positive and 5% negative, Planada 70% positive and 30% negative, Primavera 85% positive and 15% negative. Strongylus spp was the only nematode found as a parasite gastrointestinal.